ISLAM AND MARXISM FROM TAN MALAKA'S PERSPECTIVE - Elfi, Elfi; Siregar, Ghazali (STAI Asy-Syukriyyah, 2024)
This study examines Tan Malaka's thoughts on the relationship between Islam and Marxism, two ideologies often perceived as contradictory. Tan Malaka, a revolutionary figure and Marxist in Indonesia, demonstrates that he does not view these ideologies as mutually exclusive but rather sees potential for them to complement each other in the struggle for social justice and equality. In his works, Tan Malaka integrates Islamic values such as social justice with Marxist concepts such as resistance against capitalism. This article employs qualitative methods and a literature review to explore how Tan Malaka unified these ideologies within the context of the revolutionary struggle in Indonesia.